2014
DOI: 10.1002/pds.3612
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate use in pregnancy and the birth prevalence of oral clefts

Abstract: Consistent with other recent epidemiologic research, first-trimester TPM exposure was associated with an elevated birth prevalence of OC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 21 publications
3
51
1
5
Order By: Relevance
“…Some earlier studies could not identify any deleterious effect of maternal migraine on the development of birth defects, but the analysis of the first part of the HCCSCA has already shown this increased risk . In the case of maternal migraine, it is not clear whether the elevated risk of cleft formation is a consequence of the illness itself or of the drugs used to alleviate its symptoms . Our present findings showed an increased risk of CPO among mothers suffering from cholelithiasis, urolithiasis or neuro‐musculoskeletal pain syndromes as well.…”
Section: Discussioncontrasting
confidence: 66%
“…Some earlier studies could not identify any deleterious effect of maternal migraine on the development of birth defects, but the analysis of the first part of the HCCSCA has already shown this increased risk . In the case of maternal migraine, it is not clear whether the elevated risk of cleft formation is a consequence of the illness itself or of the drugs used to alleviate its symptoms . Our present findings showed an increased risk of CPO among mothers suffering from cholelithiasis, urolithiasis or neuro‐musculoskeletal pain syndromes as well.…”
Section: Discussioncontrasting
confidence: 66%
“…The increased risk of oral clefts with topiramate was subsequently confirmed in other studies. 26,27 However, the magnitude of the signal for lamotrigine was not confirmed with a larger sample size. 13,28 Thus, when PERs are inadequately powered to study associations for specific MCMs, a much larger number of exposed infants must be surveyed to base an estimate of risk with greater certainty.…”
Section: Target Sample Size and Power Considerationsmentioning
confidence: 88%
“…NAAPR has also observed a 10-fold increase in the rate of oro-facial clefts among infants exposed to topiramate monotherapy compared to unexposed [15]. A multi-database cohort study recently reported a prevalence of non-syndromic oral clefts 5.4 times higher among children exposed to topiramate in utero compared to unexposed children [16].…”
Section: Different Types Of Mcmsmentioning
confidence: 97%